Electric power transfer in spin-pumping experiments. (8th December 2017) - Rogdakis, Konstantinos; Alfert, Noah; Srivastava, Anand; Robinson, Jason W. A.; Blamire, Mark G.; Cohen, Lesley F.; Kurebayashi, Hidekazu
Abstract: Spin pumping has become an established method for generating voltages using magnetic dynamics. The standard detection method of spin pumping is based on open-circuit voltage measurement. In this study, we demonstrate that it is also possible to measure the associated electric current by using macroscopic closed circuitry. Using variable load resistors connected in series to the sample, we quantified the charge currents and associated electric power dissipation with respect to the load resistance. Through basic circuit analysis, we can describe spin-pumping cells as a non-ideal voltage source or an equivalent current source with an internal resistor.